Optimal Betti Numbers of Forest Ideals - Goff, Michael (The Electronic Journal of Combinatorics, 2009)
We prove a tight lower bound on the algebraic Betti numbers of tree and forest ideals and an upper bound on certain graded Betti numbers of squarefree monomial ideals.